Advances in Switchable RAFT Polymerization. Issue 1 (April 2015) - Moad, Graeme; Keddie, Daniel; Guerrero‐Sanchez, Carlos; Rizzardo, Ezio; Thang, San H.; Kitayama, Tatsuki; Aoshima, Sadahito; Kamigaito, Masami
Summary This paper reviews recent developments in RAFT Polymerization with proton switchable RAFT agents. We report on the successful use of N‐methyl‐N‐(4‐pyridinyl) dithiocarbamates RAFT agents for controlling the polymerization of N, N‐dimethylacrylamide (DMAm) in aqueous media, the dependence of the RAFT agent activity on acid type and acid strength (for best results a stoichiometric amount of a strong acid should be used), and the synthesis of block copolymers such as poly(DMAm)‐block‐poly(N‐vinylpyrrolidone). We describe a new class of switchable RAFT agents, the N‐aryl‐N‐(4‐pyridinyl) dithiocarbamates. These RAFT agents are more active with more activated monomers (MAMs) in protonated (switched) form and more active with less activated monomers (LAMS) in non‐protonated (unswitched) form. Finally we examine the dependence of RAFT polymerization of N‐vinylcarbazole (NVC) on the type of RAFT agent used (dithiobenzoate, trithiocarbonate, xanthate, switchable dithiocarbamate). Contrary to popular belief, NVC does not behave as a typical LAM, its polymerization is best controlled with a trithiocarbonate RAFT agent, and NVC should be described as an intermediate activity monomer (IAM).